The cooperative language learning technique with literature as resource in a Malaysian ESL classroom - Mangalam, Clamentine (International Islamic University Malaysia, 2000)
Research to present effective approaches to language teachin is an ongoing movement. This study explores the notion of a learner-centred technique of leaning English and explains the relevance of using literary materials as a resource for language learning. The study examines how students can have a new perspective of learning through the cooperative language learning technique and provides tasks based on literary materials as transmission model of teaching to a process orientated participatory model, seeing learners as acttive agents in their learning. Classroom observations, interviewss and questionnaire were the instruments used in this research. The observations examined interactions under foru main headings: Pedagogical Moves, Social Skills, Rhetorical Acts and Teacher Talk. Fourteen different categories were examined. The questaionnaire inquired into the learners' learning preferences and the interviews and certain questions in the questionnaire probed learners' attitudes towards the use of literry materials in the ESL classroom. The t-Test statistical analysis of the data for observations demonstratied significant differences for Pedagogical Moves, Social Skills and Rhetorical Acts. In the Teacher Talk group there was no significant difference. The analysis suggests that learners employ interactions that involve pedagogical moves, social skills and rhetorical acats for the completion of tasks under the cooperative language learning. The results imply that there is a positive inclination towards the learner-centred cooperative mode of language learning. Next, the paired t-Test results for the questionnaire data indicated learners' preference for the cooperative learning technique. To analyse students' attitudes towards the use of literary materials in the language classroom, a percentage calculation indicated thaat 70% of the subjects preferred the inclusion of literary materials in the ESL classroom while 30% were not in favour. There are some pedagogical implications from the findings of this research. The teaching implications provides in this study fo not intend to be exhaustive but as a guide for teachers wishing to take this aspect of teaching.